An Embedded Nonlinear Model Predictive Formation Controller for Low-Cost Architectures - Sousa, Diego; Nascimento, Tiago P.; Brito, Alisson V. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2016: Anais do VI Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2016)
The purpose of this study is to adapt and embed a navigation system and control mobile robots, based on nonlinear model predictive formation control (NMPFC), in a low-cost commercially available board. The system must provide sufficient computational resources so that the robot is able to converge, without losing performance, using the same prediction and control horizons applied in a laptop. The obtained results demonstrate that it is possible to use low-cost boards applying the embedded navigation and control system of mobile robots into the proposed scenario, using the same predictive and control horizons applied in a laptop.